SULTANATE PERIOD: A BRIEF ESTIMATION OF BENGALI LITERATURE - Sarwar, Firoj High (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The materialization of Sultanate rule over Bengal territory by the onset of thirteen century marked a new sketch on socio-cultural life of native people. For the first time, dominated Hindu society encountered a new wind of Muslim rule, which gradually made a socio-cultural cocktail for both communities. Obviously due to this shift, the Bengali literature received a new sway under new political set up. Under the Influence of contemporary socio-political thoughts, the theme, pattern, volume and expression of Bengali literature progressively got new line. Consequently, there certain streamline became as new trends for the Bengali literature that clearly distinct from the earlier times. Simply, this paper has made an endeavor to investigate the trend and the line of changes that had been taken place in Bengali literature during sultanate rule in India.